ANALISIS PERAN AKUNTABILITAS LAPORAN KEUANGAN PEMERINTAH DAERAH TERHADAP TINGKAT INDEKS TATA KELOLA PEMERINTAHAN (Studi Kasus Pada Pemerintahan Provinsi Se-Indonesia) - Tika Septiani (Jurusan Akuntansi Politeknik Negeri Bandung, 2017)
Abstract: This research is conducted to analyze the accountability of local government financial report have significant influence to level of Indonesian Governance Index (IGI). Case study on provincial government throughout Indonesia. This research uses descriptive analysis method. The data used secondary data with using the local government financial report from Badan Pemeriksa Keuangan (BPK). Badan Pemeriksa Keuangan (BPK) is a state high institution in the Indonesian state administration system which has the authority to examine the management and responsibility of state and local finances. Hypothesis testing using t test and multiple regression analysis, obtained the form of equation Y = 18,023 - 0,180 X1 + 0,593 X2 + 0,034 X2 + e, and coefficient of determination (R2) equal to 76,3%. From the results of research and hypothesis testing conducted it can be concluded that accountability of local government financial statements have a significant effect on the index of good governance.Keywords: Accountability, Good Government Governance